2015
DOI: 10.1371/journal.pntd.0003994
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Helminth Infection in Active Tuberculosis Is Associated with Increased Regulatory and Th-2 Responses and a Lower Sputum Smear Positivity

Abstract: BackgroundThe impact of intestinal helminth infection on the clinical presentation and immune response during active tuberculosis (TB) infection is not well characterized. Our aim was to investigate whether asymptomatic intestinal helminth infection alters the clinical signs and symptoms as well as the cell mediated immune responses in patients with active TB.MethodologyConsecutive, newly diagnosed TB patients and healthy community controls (CCs) were recruited in North-west Ethiopia. TB-score, body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 36 publications
5
59
2
1
Order By: Relevance
“…Similar results were found in Ethiopia in patients with and without tuberculosis; prevalence of intestinal helminths (being S. stercoralis one of the most frequent one) was 71% in patients with tuberculosis and 36% in healthy household contacts, yielding an odds ratio of 4.7 . A study performed in the same setting showed that patients with tuberculosis and helminth co‐infection had a lower rate of sputum smear positivity than those without helminth co‐infection . More examples of the helminth co‐infection effect have been described in HIV‐infected patients in the tropics, where the presence of intestinal nematodes is associated with decreased CD4+ T‐cell count even under antiretroviral treatment .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were found in Ethiopia in patients with and without tuberculosis; prevalence of intestinal helminths (being S. stercoralis one of the most frequent one) was 71% in patients with tuberculosis and 36% in healthy household contacts, yielding an odds ratio of 4.7 . A study performed in the same setting showed that patients with tuberculosis and helminth co‐infection had a lower rate of sputum smear positivity than those without helminth co‐infection . More examples of the helminth co‐infection effect have been described in HIV‐infected patients in the tropics, where the presence of intestinal nematodes is associated with decreased CD4+ T‐cell count even under antiretroviral treatment .…”
Section: Discussionsupporting
confidence: 65%
“…Helminth infections in humans may modify the immune response to other infections or even the antibody production after vaccination . Some examples of how S. stercoralis may modify the immune response against other infections have been described in tuberculosis or malaria . Our group has recently reported how a helminth infection (mostly strongyloidiasis) may modulate the microbiological findings in patients with chronic Chagas disease: S. stercoralis infection was associated with significantly higher proportion of positive T. cruzi DNA detection in peripheral blood .…”
Section: Introductionmentioning
confidence: 92%
“…A more recent study in Ethiopia, however, indicated that, in patients with asymptomatic helminth infection, active TB is associated with lower rates of sputum smear positivity, leading to the conclusion that there was a beneficial effect of helminth infection on bacterial burdens [61]. Moreover, a randomized double blind clinical trial examining the effect of anti-helmintic treatment on clinical improvement of TB after 2 months showed no significant effect of anti-helmintic (albendazole) treatment over placebo [62].…”
Section: Helminth - Tuberculosis Co-infectionmentioning
confidence: 99%
“…For example, it has been shown that intestinal helminth co-infection is accompanied by lowered in vitro production of IFNγ and elevated production of IL-10 in individuals with active pulmonary tuberculosis [60]. Similarly, it was also recently shown that helminth infections with coincident active TB have marked decreases in dual-functional Th1 and Th17 cell frequencies [77] which, in one study at least, may be associated with increased Treg and Th2 responses [61]. …”
Section: Helminth - Tuberculosis Co-infectionmentioning
confidence: 99%
“…TB patients with concomitant helminth infections present with reduced frequencies of peripheral T cells as well as more severe radiological findings of pulmonary TB disease [173]. Asymptomatic helminth infection was shown to be associated with increased Treg and Th2 responses and a lower rate of sputum smear positivity [174]. Although deworming with albendazole failed to improve clinical symptoms, there was a significant decline in eosinophils and IL-10 production along with weight gain observed in the deworming group compared with placebo 3 months post-treatment [175].…”
Section: Tb/helminth Co-infectionmentioning
confidence: 99%